Assessment of Solid Waste Management Performance in Urban Areas - Utama, Ahmad Rikia Tri; Costa, Maria Isabel; Zhou, Chuanbin (RESWARA: Jurnal Riset Ilmu Teknik, 2024)
Rapid urbanization has intensified the challenges of municipal solid waste management (MSWM) in cities worldwide, particularly in developing countries. Inefficient collection systems, limited recycling, inadequate disposal practices, and weak governance continue to undermine environmental quality and public health. This article aims to assess solid waste management performance in urban areas through a comprehensive synthesis of empirical studies and performance assessment frameworks published between 2015 and 2024. The study employs a systematic qualitative assessment approach, reviewing peer‑reviewed journal articles, book chapters, and dissertations indexed in international databases. The analysis focuses on key performance dimensions, including waste generation, collection efficiency, treatment and recycling rates, disposal practices, institutional capacity, and community participation. The results indicate that most urban areas exhibit low to moderate performance levels, with significant disparities between cities and regions. Socio‑economic development, governance quality, availability of infrastructure, and public awareness emerge as the most influential factors affecting MSWM performance. Comparative evidence from Asia, Africa, Europe, and Latin America reveals that cities adopting integrated assessment indicators and participatory governance models tend to achieve better outcomes. This study concludes that improving urban solid waste management requires integrated performance assessment tools, stronger policy enforcement, and sustained community engagement. The findings provide valuable insights for policymakers and urban planners seeking to enhance sustainable waste management systems in rapidly urbanizing contexts.